1996
DOI: 10.1557/proc-449-149
|View full text |Cite
|
Sign up to set email alerts
|

MBE Growth of (In)GaN for LED Applications

Abstract: We report on essential aspects of the growth of InGaN / GaN p-n junctions by gas-source molecular beam epitaxy (MBE) and present the first blue and green electroluminescence from such structures grown entirely by MBE.A study of the growth conditions for a GaN nucleation layer on sapphire and for the subsequent growth of undoped GaN points out the necessity for Ga-stabilized growth. Unintentionally doped GaN grown at 1 μm/h shows background doping levels below 1017 cm-3 and mobilities up to 320 cm2/Vsec (at 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 14 publications
6
40
0
Order By: Relevance
“…As has been previously observed [2][3][4], the RHEED image abruptly changes from spotty to streaky as flux conditions move from nitrogen-rich to gallium-rich. The surface morphology of films grown on GaN buffer layers and under various flux conditions is shown in Figure 1.…”
Section: Gan Buffer Layerssupporting
confidence: 72%
“…As has been previously observed [2][3][4], the RHEED image abruptly changes from spotty to streaky as flux conditions move from nitrogen-rich to gallium-rich. The surface morphology of films grown on GaN buffer layers and under various flux conditions is shown in Figure 1.…”
Section: Gan Buffer Layerssupporting
confidence: 72%
“…Second, the calculated growth rates of ternary compounds GaInN differs significantly from that measured in Ref. [33], even under a very wide variation of the growth parameters. The origin of this inconsistency may be attributed to a possible occurrence of decomposition of InN into the liquid and vapor phases during the experiments of Ref.…”
Section: Footnotesmentioning
confidence: 55%
“…The breakthrough in the study of growth kinetics in PAMBE came with the finding that, in Ga-rich conditions, it is possible to grow relatively smooth layers at low growth temperatures [7,[10][11][12][13][14]16]. However, such growth conditions were prone to the formation of Ga droplets on the GaN surface and high-quality material was mainly formed in the regions between the droplets.…”
Section: Growth Conditions For Pambementioning
confidence: 99%
“…In the more widely employed plasma-assisted MBE (PAMBE) [5], purified nitrogen gas is activated using an RF-plasma and supplied to the growth surface at typical flow rates of 1-2 sccm. Early experimental results [7] showed that unlike ammonia MBE, PAMBE requires group III-rich conditions to achieve good material quality. Much progress has been made in both theoretical [8,9] and experimental [10][11][12][13] understanding of the growth kinetics for such metal-rich conditions.…”
Section: Introductionmentioning
confidence: 99%